Iodine/EtOH: A Novel and Versatile Catalyst for the Synthesis of β-Amino Ketones via Three Component Reaction - Yadav, Jhillu S.; Reddy, Basi V.S.; Shankar, Kattela S.; Premalatha, Kokku; Swamy, Tallapally (Letters in Organic Chemistry, 2008)
A variety of β-amino ketones are readily prepared in high yields and with good to excellent anti selectivity under extremely mild conditions by means of three component coupling of aromatic aldehydes, aryl amines and ketones using 10 mol% of molecular iodine in ethanol. The use of readily available iodine makes this process quite simple, more convenient and cost-effective.
Keywords: β-amino carbonyls